MENGUCAPKAN SALAM TERHADAP NON MUSLIM DALAM PERSPEKTIF HADIS - Idris Siregar (UIN Sumatera Utara Medan, 2019)
Salam are often spoken as the beginning of coversations between individuals who are social beings. Interaction with fellow Muslims often begins with salam. This is a practice used in Islam. Then what about the salam between Muslims and non-Muslims? As social beings, humans do not only interact with people who share their beliefs. But also with people with different beliefs. To explore the traditions relating to this matter, the method of the Takjrij Hadith is the easiest way to find out the traditions related to this issue. So that the status of the hadith is known, that is a valid Hadith whose quantity is Saheh. Starting salam against non-Muslims is not allowed, but the answer may be with a variety of answers based on the hadith of the Prophet. Along with the times, the scientific forums are not only filled with Muslims. What if a Muslim starts greeting publicly in a scientific forum? Some Ulama allow for reasons of intent, emergency and there is a cause.